P10 Evaluation of existing line-locking practice in central venous catheters of paediatric patients on home parenteral nutrition. Issue 2 (19th January 2018) - Amy, Tustin; Karen, Hartley; David, Derry; Julian, Thomas
Abstract : Aim: To review current line-locking practice of central venous catheters (CVCs) to reduce catheter related blood stream infections (CRBSIs) and preserve line integrity in paediatric patients on home parenteral nutrition (HPN), with the secondary aim of producing a concise, evidence-based guideline for use in this cohort and inpatient PN patients as well. Method: All 19 paediatric HPN patients were reviewed retrospectively over 6 months (January–June 2017). Data was collected from clinic letters, HPN prescriptions and blood cultures. Information gathered per patient: Line lock(s) Infective episode(s) CVC replacement(s) Establishment of current practice: All patients use TaurolockTM first-line. If CVC is stiff or stops bleeding back switch to TauroLockTM-Hep100. Should problems persist introduce alcohol 70% on alternate days or alone if recurrent infections occur on TaurolockTM. Blocked CVCs are instilled with urokinase or alteplase and CVC replaced if unsuccessful. Results: 18/19 patients were prescribed line locks as per above practice. One patient is prescribed heparin 10units/ml – due to a documented TauroLockTM allergy – and remained infection- free throughout. 7 infections occurred overall in 6 patients with 13 patients infection-free. 2.2 infections/1000 catheter days occurred in patients on TauroLockTM with 2 patients requiring CVC changes due to infection and broken CVC respectively. 1 infection/1000 catheter days occurred on TauroLockTM- Hep100 with 2 CVC changes required due to occlusion. 11 infections/1000 catheter days occurred in 1 patient on daily alcohol 70%, although result validity is uncertain due to potential contamination of blood culture specimen from skin organisms during sampling. No infections occurred in 248 catheter days in patients alternating TauroLockTM-Hep100 and alcohol 70% with one line change required as CVC moved position. Conclusion: CRBSIs pose a serious problem in paediatric HPN patients. 1, 2 Taurolidine has proven efficacy at preventing CRBSIs and proven superiority to heparin. 3 The effectiveness of alcohol at reducing CRBSI rates and preventing CVC replacement has been proven when compared to heparin4 however, due to adverse effects (thrombosis and CVC degradation) 4 use is limited to ensure benefits outweigh risks. These studies, although limited, and results in our patient cohort support the continued use of these line locks as per existing practice. Future work includes need to formalise written guideline and discuss clear pathway if patients have multiple CRBSIs on their existing line lock as presently information is unclear. References: Koletzko B, Agostoni C, Ball P, et al. ESPEN/ESPGHAN guidelines on paediatric parenteral nutrition. Journal of Paediatric Gastroenterology and Nutrition2005;41:S76–S84. Candusso M, Faraguna D, Sperli D, et al. Outcome and quality of life in paediatric home parenteral nutrition. Current Opinion in Clinical Nutrition and Metabolic Care2005;5:309–14. Chu HP, Brind J, Tomar R, et al. Significant reduction in central venous catheter-related bloodstream infections in children on HPN after starting treatment with taurolidine line lock. J Pediatr Gastroenterol Nutr2012;55:403–7. Oliveira C, Nasr A, Brindle M, et al. Ethanol locks to prevent catheter-related bloodstream infections in parenteral nutrition: A meta-analysis. Paediatrics2012;129:318–329.